BACTERIAL PROFILE WITH ANTIBIOTIC STUDY OF PYODERMA - A. N. VEDPATHAK; M. R. JADHAV; P. J. MISAL (The Bioscan, 2011)
Pyoderma is a group of various skin diseases and its accurate diagnosis is most important. Micro organisms can infect healthy skin, but more often they infect skin already damaged by an injury or an abrasion. So, bacterial skin infections have been considered as possible common health hazard. In present investigation, 25 samples were collected and out of that Staphylococcus was found to be a causative agent for pyodermal infections. Two strains of Staphylococcus were found on the basis of coagulase test. Out of total Staphylococcus isolated, 21 of them were coagulase positive and 4 of them were coagulase negative. Antibiotic sensitivity pattern revealed maximum resistance to penicillin (85%), followed by ciprofloxacin (60%), vancomycin (60%). The organism were most sensitive towards linezolid (85%) followed by gentamycin (75%), and oxacillin (70%).